Analysis of Human Resource Development in The Era of Digital Transformation: A Case Study at The Regional Secretariat of Southeast Sulawesi Province - Ode Ompo, La Musu; Adam, Pasrun; Sabilalo, Mahmuddin A. (International Journal of Management and Education in Human Development, 2024)
a